Crack Corrosion Simulation of H62 Copper Alloy Coating Under Damage Condition. (November 2020) - Tong, Zhang; Wentao, NIU; Qing, Dong; Cheng, Xia
Abstract: Objective To study the crevice corrosion under the condition of damaged coating. Methods The simulation was carried out by using COMSOL software. The influence of the distance between the damage zone ( W ) and the gap width ( H ) of the damage zone was discussed. As a result, the corrosion enters the stable corrosion stage after a very short initial stage, and the current is much longer than the stable stage in the initial stage. The electrolyte potential and the electrode potential are completely different in the initial and stable stages; the anode reaction occurs uniformly in the damaged area, and the cathode reaction focuses on the crack mouth in the stable stage; the increase of W and H is aggravated by corrosion, but when W is greater than 0.7mm, the effect is very weak and can be considered to be stable. Conclusion The crevice corrosion under the condition of coating damage is the corrosion controlled by the cathode oxygen reduction reaction. The oxygen is quickly consumed in the initial stage and cannot be replenished. The cathodic reaction is mainly concentrated in the crack mouth. The change of W at small time will affect the corrosion. The increase in H will exacerbate corrosion.